2007
DOI: 10.1128/iai.01535-06
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Host Chemotactic Response byEncephalitozoonspp

Abstract: Microsporidians are a group of emerging pathogens typically associated with chronic diarrhea in immunocompromised individuals. The number of reports of infections with these organisms and the disseminated pathology is growing as diagnostic tools become more readily available. However, little is known about the innate immune response induced by and generated against these parasites. Using a coculture chemotaxis system, primary human macrophages were infected with Encephalitozoon cuniculi or Encephalitozoon inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Pathology and epidemiological reports have identified immune effector cells at sites of infection (32) and detected increased levels of serum antibodies for microsporidia in humans (17,39). Recent in vitro studies have shown that infections lead to the production of numerous cytokines and chemokines, including TNF-␣, CCL2, CCL3, and CCL4 (12,14). Although these responses have been well documented, to date, no known receptor involved in microsporidian recognition and signaling has been identified.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pathology and epidemiological reports have identified immune effector cells at sites of infection (32) and detected increased levels of serum antibodies for microsporidia in humans (17,39). Recent in vitro studies have shown that infections lead to the production of numerous cytokines and chemokines, including TNF-␣, CCL2, CCL3, and CCL4 (12,14). Although these responses have been well documented, to date, no known receptor involved in microsporidian recognition and signaling has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Spores were washed once in PBS containing 0.2% Tween 20, resuspended in supplemented DMEM, and counted with a hemacytometer (9). Spores were used at a 5:1 spore-to-MDM ratio (12). Some spores were heat inactivated in a 95°C water bath for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations